Adenosine Testing in Atrial Flutter Ablation: Unmasking of Dormant Conduction Across the Cavotricuspid Isthmus and Risk of Recurrence. (23rd May 2013) - MORALES, GUSTAVO X.; MACLE, LAURENT; KHAIRY, PAUL; CHARNIGO, RICHARD; DAVIDSON, EVAN; THAL, SERGIO; CHING, CK; LELLOUCHE, NICOLAS; WHITBECK, MATTHEW; DELISLE, BRIAN; THOMPSON, JENKS; DI BIASE, LUIGI; et al.
Adenosine Unmasking Dormant Conduction Across the Cavotricuspid Isthmus: Background: Adenosine‐induced hyperpolarization may identify pulmonary veins at risk of reconnection following electrical isolation for atrial fibrillation. The potential role of adenosine testing in other arrhythmic substrates, such as cavotricuspid isthmus (CTI)‐dependent atrial flutter, remains unclear. We assessed whether dormant conduction across the CTI may be revealed by adenosine after ablation‐induced bidirectional block, and its association with recurrent flutter. Methods and Results: Patients undergoing catheter ablation for CTI‐dependent flutter were prospectively studied. After confirming bidirectional block across the CTI by standard pacing maneuvers, adenosine (≥12 mg IV) was administered to assess resumption of conduction, followed by isoproterenol (ISP) bolus. Further CTI ablation was performed for persistent (but not transient) resumption of conduction. Bidirectional block across the CTI was achieved in all 81 patients (63 males), age 61.2 ± 11.0 years. The trans‐CTI time increased from 71.9 ± 18.1 milliseconds preablation to 166.2 ± 26.4 milliseconds postablation. Adenosine elicited resumption of conduction across the CTI in 7 patients (8.6%), 2 of whom had transient recovery. No additional patient with dormant conduction was identified by ISP. Over a follow‐up of 11.8 ± 8.0 months, atrial flutter recurred in 4 (4.9%) patients, 3/7(42.9%) with a positive adenosine challenge versus 1/74 (1.3%) with a negative response, P = 0.0016 (relative risk 31.7). Conclusion: Adenosine challenge following atrial flutter ablation provoked transient or persistent resumption of conduction across the CTI in almost 9% of patients and identified a subgroup at higher risk of flutter recurrence. It remains to be determined whether additional ablation guided by adenosine testing during the index procedure may further improve procedural outcomes.